Perception of COVID-19 Pandemic Among Residents of a High Density – Low Income Area in Enugu City, Nigeria - Chukwuebuka Okafor; Christian Madu; Charles Ajaero; Henrietta Ajaero; Chinelo Nzekwe; Loveline Nebo (Technium Social Sciences Journal, 2020)
Coronavirus (COVID-19) infection is increasing steadily in Nigeria. The aim of this study is to assess the perception of people living in low income and densely populated area about COVID-19. This study was carried out in one of the most popular low income area (Abakpa-Nike) in a major city in South East, Nigeria (Enugu). Four hundred questionnaires were administered to heads of the household in this community. A return rate of 77.5% was achieved. Descriptive (frequency, percentages, weighted average and median) and inferential statistics were used for the study. Our tests show that females are more likely to use facemask more frequently than males (p=0.000). However, there is no association between gender and frequent use of hand sanitizers (p=0.06). also, no association exists between gender and regular observation of social distancing (p=0.272). There was also an association between educational status and perception that Nigeria’s tropical climate “kills” COVID-19 virus (p=0.021). No association exist between educational status and the perception that Nigerians immune system is “stronger” than COVID-19 virus (p=0.147). Therefore, National Center for Diseases and Control, Presidential Task Force on COVID-19 and pertinent state agencies should put into consideration educational attainment and economic status of the people in communication output.